Corpos Invisíveis: Uma Análise Sobre Os Territórios Da Prostituição Travesti Em Santarém/Pa - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
This paper analyzes the spatialities that are territorialized by transvestites in Santarém/PA, for the practice of prostitution, in two spatial areas: along the BR-163 highway and near the Prainha district waterway terminal. In the chapters of this study, we gradually present the issues that permeate the existence of transvestite subjects, who are the focus of the research. Thus, it is understood that, according to the different forms of exclusion and violence, it is in prostitution that transvestites find ways of surviving. A bibliographical review was carried out, although it has been little discussed and explored in geographical science, as well as photographic records of the locations analyzed. In this way, it became possible to understand the problem presented, as well as the spatial elements that corroborate the choice of spaces for the construction of territories, understood as temporary for transvestites, as well as the conjunctures that cause the dissolution of these territorialities.
Keywords: Territórios; territorialidades; prostituição; travestis; CIÊNCIAS HUMANAS